1971
DOI: 10.1029/ja076i019p04381
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotail changes in relation to the solar wind magnetic field and magnetospheric substorms

Abstract: Substorm activity is known to be associated with changes in the solar wind parameters and the magnetotail configuration. In this paper we investigate whether the magnetotail changes occur only as a consequence of substorms or also as a direct consequence of changes in the solar wind parameters. Using data from several satellites (Ogo 5, ATS 1, Imp 4, Explorer 33 and 35) and 17 ground magnetic observatories, we conclude that the tail responds to both changes in the north‐south orientation of the interplanetary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(58 citation statements)
references
References 17 publications
3
55
0
Order By: Relevance
“…lijima (1972) and McPherron (1973) have also employed the technique of keying on the temporally-isolated low-latitude onset time to confirm and quantify previous results of Fairfield and Ness (1970) and Aubry and McPherron (1971) concerning pre-and post-onset variations of the tail-lobe magnetic energy density. The results of McPherron (1973), which are similar to.those of lijima (1972) are shown in Figure 2.…”
Section: Tail-lobe Magnetic Variationsmentioning
confidence: 77%
See 1 more Smart Citation
“…lijima (1972) and McPherron (1973) have also employed the technique of keying on the temporally-isolated low-latitude onset time to confirm and quantify previous results of Fairfield and Ness (1970) and Aubry and McPherron (1971) concerning pre-and post-onset variations of the tail-lobe magnetic energy density. The results of McPherron (1973), which are similar to.those of lijima (1972) are shown in Figure 2.…”
Section: Tail-lobe Magnetic Variationsmentioning
confidence: 77%
“…Such adjustments of large-scale magnetospheric flow patterns often can be inferred from phenomena such as ground magnetic variations at polar-cap and equatorial latitudes (Nishida and Kokubun, 1971;, variations in tail-lobe magnetic energy density (Aubry and McPherron, 1971;Nishida and Nagayama, 1973;Meng and Colburn, 1973), and latitudinal shifts of dayside auroras and the associated F-layer irregularity.zones or FLIZ . Quantitative studies of such phenomena as they -14 -respond to changes in the strength and direction of .the INF are beginning to yield important new information on the nature of the interaction between the interplanetary and geomagnetic fields.…”
Section: The Interplanetary Magnetic Field and Magnetospheric Convectionmentioning
confidence: 99%
“…We note that for this event, we have no means of precisely determining the arrival time of the southward field at the magnetopause. As discussed originally by Aubry and McPherron [1971], it is reasonable to assume that the solar wind convection time is a good estimate of the delay.…”
Section: Substormsmentioning
confidence: 99%
“…Aubry and McPherron [1971] and Caan et al [1975Caan et al [ , 1978 observed that the magnetic field strength in the tail lobes decreases at expansion phase onset, implying the removal of magnetic flux from the lobes. This observation is not conclusive regarding the exact timing of the increase in magnetotail reconnection, however.…”
Section: Introductionmentioning
confidence: 99%